2005
DOI: 10.1211/jpp.57.9.0017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cytotoxic effect of the monoterpene indole alkaloid echitamine in-vitro and in tumour-bearing mice

Abstract: The cytotoxic effect of various concentrations of echitamine chloride was studied in HeLa, HepG2, HL60, KB and MCF-7 cell lines in-vitro and in mice bearing Ehrlich ascites carcinoma (EAC). Exposure of various cells to different concentrations of echitamine chloride resulted in a concentration-dependent cell killing, and KB cells were found to be most sensitive amongst all the cells evaluated. EAC mice treated with 1, 2, 4, 6, 8, 12 or 16 mg kg-1 echitamine chloride showed a dose-dependent elevation in the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…[2] As a result, scientists have investigated the pharmacological effects of akuammiline alkaloids and discovered their wide range of biological properties, which span from anticancer to analgesic effects. For example, (À)-echitamine (1), which was first isolated in 1875, [3] displays both in vitro and in vivo cytotoxicity, [4] whereas (+)-strictamine (2) [5] inhibits the transcription factor NF-kB ( Figure 2). [6] Additionally, derivatives of (+)-picraline (3) [7] inhibit the renal cortex protein SGLT2, [8] while (À)-aspidophylline A [(À)-4] reverses drug resistance in cancerous cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…[2] As a result, scientists have investigated the pharmacological effects of akuammiline alkaloids and discovered their wide range of biological properties, which span from anticancer to analgesic effects. For example, (À)-echitamine (1), which was first isolated in 1875, [3] displays both in vitro and in vivo cytotoxicity, [4] whereas (+)-strictamine (2) [5] inhibits the transcription factor NF-kB ( Figure 2). [6] Additionally, derivatives of (+)-picraline (3) [7] inhibit the renal cortex protein SGLT2, [8] while (À)-aspidophylline A [(À)-4] reverses drug resistance in cancerous cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other antineoplastic agents like, doxorubicin, vinblastine, taxol and teniposide (VM-26) have been reported to induce cytotoxicity in V79 cells [11,[39][40][41][42]. Treatment of HeLa, MCF-7, HL 60, or KB cells to alcoholic extract of the stem bark of Alstonia scholaris or echitamine chloride have been reported to induce cytotoxicity earlier [8,20,43,44]. The cytotoxic effect of APE is reflected in proliferation indecies (PI), where a concentration dependent reduction in PI was observed at all post-treatment times in cells treated with various concentrations of APE.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the thirteen indole alkaloids isolated from the root bark of sister species A. macrophylla, the pronounced cytotoxic activity has been found for bisindoles O-acetylmacralstonine, villalstonine and macrocarpamine against the human cancer cell lines, MOR-P (adenocarcinoma), COR-L23 (large cell carcinoma), StMI1 1a (melanoma), Caki-2 (renal cell carcinoma), MCF7 (breast adenocarcinoma) and LS174T (colon adenocarcinoma) [55]. The alkaloid echitamine, present in the stem bark of A. scholaris has been reported to be cytotoxic in vitro and in vivo [56].…”
Section: Issn: 2470-1017mentioning
confidence: 99%
“…Echitamine chloride, one of the constituent of ASE has been reported to inhibit DNA synthesis [60][61]. Our earlier study has indicated that presence of echitamine chloride in ASE and its cytotoxic effects in vitro and in vivo [56]. It may also have acted by inhibiting serine proteases.…”
Section: Issn: 2470-1017mentioning
confidence: 99%